2020
DOI: 10.1186/s12887-020-02283-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of pituitary volume in girls with precocious puberty

Abstract: Background: To date, the gonadotropin-releasing hormone (GnRH) stimulation test is still the gold standard for precocious puberty (PP) diagnosis. However, it has many disadvantages, including low sensitivity, high cost, and invasive operation. This study aims to evaluate whether magnetic resonance imaging (MRI)-derived variables, including pituitary volume (PV), could be used as diagnostic factors for PP in girls, providing a non-invasive diagnostic approach for PP. Methods: A total of 288 young female patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…Other investigators recommended basal LH levels instead of GnRHST, but the cutoff values of basal LH varied from 0.1 to 0.83 IU/L (ICMA) with 64% to 93% diagnostic sensitivity ( 18 , 19 ). Similarly, pelvic ultrasonography or pituitary magnetic resonance imaging could not distinguish prepubertal and pubertal stages ( 20 , 21 ). As a major inhibitor of hypothalamic GnRH secretion, serum MKRN3 concentration declines before puberty onset in girls and might be useful for the assessment of pubertal development ( 22 ); however, it is also invasive.…”
Section: Discussionmentioning
confidence: 96%
“…Other investigators recommended basal LH levels instead of GnRHST, but the cutoff values of basal LH varied from 0.1 to 0.83 IU/L (ICMA) with 64% to 93% diagnostic sensitivity ( 18 , 19 ). Similarly, pelvic ultrasonography or pituitary magnetic resonance imaging could not distinguish prepubertal and pubertal stages ( 20 , 21 ). As a major inhibitor of hypothalamic GnRH secretion, serum MKRN3 concentration declines before puberty onset in girls and might be useful for the assessment of pubertal development ( 22 ); however, it is also invasive.…”
Section: Discussionmentioning
confidence: 96%
“…35 ROC analysis showed that PV could be a marker for CPP. 13 Pituitary measurements varied in small-sized children in different age groups with 2D MR images. 36 Compared to previous research, 13 a radiomics signature model with features extracted from 3D MR images in our study had improved diagnostic value and also had higher net benefit than aPV and aPH models based on DCA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Pituitary measurements varied in small-sized children in different age groups with 2D MR images. 36 Compared to previous research, 13 a radiomics signature model with features extracted from 3D MR images in our study had improved diagnostic value and also had higher net benefit than aPV and aPH models based on DCA analysis. In details, the original_shape_MinorAxisLength and Maximum2DDiameterRow were significantly associated with HPG axis activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations